Focused Approach Towards Internal Audit (IA) Planning to Safeguard Companies from Any Internal and External Risks - Singh Grover, Randeep (Digital Repository of Theses, 2025)
In the contemporary business landscape, traditional internal audit planning methodologies have become increasingly inadequate for addressing the complex, dynamic challenges organizations face. This research introduces a transformative 7-Step Strategic Risk Assessment Framework that revolutionizes internal audit planning from a reactive compliance function to a proactive strategic partner. The research addresses critical organizational challenges by developing a comprehensive approach that integrates quantitative and qualitative risk assessment techniques. The framework systematically synthesizes inputs from Enterprise Risk Management (ERM), financial metrics, industry studies, business strategies, and stakeholder insights to create a holistic audit plan. The 7-step methodology encompasses a thorough examination of audit universe, historical coverage analysis, identification of unaudited units, stakeholder engagement, strategic insights, control effectiveness evaluation, and digital transformation risk assessment. By incorporating a 7-factor risk approach that balances quantitative metrics like financial materiality with qualitative factors such as regulatory changes and emerging industry risks, the framework provides a 360-degree view of potential organizational vulnerabilities. Key outcomes demonstrate significant improvements in audit effectiveness, including expanded audit coverage, enhanced stakeholder confidence, and transformation of the internal audit function into a value-generating organizational asset. The approach enables organizations to proactively mitigate risks, fortify internal controls, drive sustainable growth, improve governance, and enhance stakeholder trust. Future research directions include exploring the framework's scalability across different organizational contexts, investigating technological integration for advanced risk modelling, and developing adaptive strategies for evolving regulatory landscapes. The research ultimately provides a blueprint for reimagining organizational risk management as a dynamic, intelligence-driven strategic capability.